4c+3c-5c=

Simple and best practice solution for 4c+3c-5c= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4c+3c-5c= equation:


Simplifying
4c + 3c + -5c = 0

Combine like terms: 4c + 3c = 7c
7c + -5c = 0

Combine like terms: 7c + -5c = 2c
2c = 0

Solving
2c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Divide each side by '2'.
c = 0

Simplifying
c = 0

See similar equations:

| -8-5x^2=-29 | | 3xn+4=-6 | | 12n+5=21 | | 14.27x=114.50x | | 3Xn+4=-62 | | 7.5x=y | | 62-39= | | 2(c-3)=1.2-x | | X-(-4)=0 | | 14.27x=9.50x | | K/3=13 | | 3(2x+5)-3x=2(x+5)-3(2x-4) | | 2(1/4x-3)-(1/3x- | | 20=1/(x-0.03) | | 14y+3814y+38= | | x/-4=-17 | | 6(x-1)+2=32 | | -32=15w-7m | | 2(5x+6)=52 | | 4(12+6w-w)-3w= | | 81/x=x/16 | | 5x+9y=-85 | | 5y+1+8y-5=180 | | 15-24x/6=5 | | 5(1+5r)= | | 3[n-6]=-5n-2 | | 15v+13=93-v | | -6x-6-7=7x+2 | | (2a+44)=(5a-4) | | 80-3=5k+8 | | -1(7k+4)+9=-13 | | 3x-1=197 |

Equations solver categories